The Suburban Origins of Redlining: A Canadian Case Study, 1935-54 - Harris, Richard; Forrester, Doris (Urban Studies, 2003)
Redlining occurs when institutions decline to make mortgage loans in specific areas. The practice originated in the 1930s, when federal agencies encouraged lenders to rate neighbourhoods for mortgage risk. Since the 1960s, especially in the US, it has been associated with disinvestment, racial discrimination and neighbourhood decline. It has always been viewed as a feature of the inner city. Historical evidence indicates that across Canada the first areas to be redlined were the less-desirable suburbs. Land registry and property assessment data establish the emergent patterns in Hamilton, Ontario. Between 1931 and 1951, institutional lending became a social norm first on new dwellings in suburbs. Individual lenders, previously dominant, were relegated to older inner-city properties or cheaper dwellings in less-desirable suburbs. In 1931, there were only minor geographical variations in the incidence of mortgage finance, and specifically of institutional financing, across the urban area. By 1951, lending institutions, led by insurance companies, were discriminating sharply in favour of the West End, the Mountain and Bartonville, and against those parts of the East End that were unserviced or close to lakefront industry. The evidence for Hamilton confirms that in Canada redlining originated in the suburbs. The same may also be true for US metropolitan areas, although the institutional context was different and relevant data are lacking.

Population Displacement and Housing Dilemmas Due to Catastrophic Disasters - Levine, Joyce N.; Esnard, Ann-Margaret; Sapat, Alka (Journal of Planning Literature, 2007)
As Hurricane Katrina revealed, coastal communities have become far more vulnerable to tropical storms and the long-term displacement of residents. Yet, because the emergency management model presumes that recovery quickly follows response, governments focus only on short-term, localized displacement. However, long-term and long-distance displacement exposes a gray area between immediate shelter and permanent housing, along with concerns about vulnerability, housing availability, and land development. We begin this article by discussing the transition between response and recovery. We then review literature regarding social vulnerability, displacement, provision of temporary housing, households' return decisions, and disaster-driven land development and housing construction processes. We close with thoughts on future research to increase planners' understanding of the issues involved and to help them craft effective policies.

Comparison of Hydrologic Responses at Different Watershed Scales - Mohamoud, Yusuf (2004)
Land surface hydrology controls runoff production and the associated transport of sediments, and a wide variety of anthropogenic organic chemicals, and nutrients from upland landscape areas and hillslopes to streams and other water bodies. Based on interactions between landscape characteristics and precipitation inputs, watersheds respond differently to different climatic inputs (e.g. precipitation and solar radiation). This study compares the hydrologic responses of the MidAtlantic watersheds, and identifies the landscape and climatic descriptors that control those responses. Our approach was to select representative watersheds from the Mid-Atlantic region, group the watersheds by physiographic province and ecoregion, and then collect landscape, climate, and hydrologic response descriptor data for each selected watershed. For example, we extracted extensive landscape descriptor data from soil, land use and land cover, and digital elevation model geographic information system (GIS) databases. After sufficient data was collected, we conducted a variety of studies to determine how different landscape and climatic descriptors influence the hydrologic response of Mid-Atlantic watersheds. This report is comprised of four main parts. Part I describes the selection of the representative study watersheds and the determination of representative physical landscape descriptors for each watershed using geographic information system analysis tools. Part II characterizes the climate and associated hydrologic responses of the study watersheds. To select climate descriptors that are good predictors of hydrologic response, we examined a large number of candidate descriptors. Based on our examination, we selected dryness index and mean monthly rainfall as the best hydrologic response predictors. In Part II, we also present the results of our study hydrologic response comparisons of the study watersheds using a water balance approach. The water balance approach was based on comparisons of precipitation, streamflow, and evapotranspiration at annual, monthly, and daily time scales. These comparisons revealed that elevation and latitudinal position strongly influence hydrologic response. The results also showed that mountainous watersheds of the Appalachian Plateau, Ridge and Valley, and Blue Ridge Physiographic Provinces have more streamflow and less evapotranspiration than watersheds located in the Piedmont Province, and that snowmelt contributes a large portion of streamflow. Part III presents relationships we derived between landscape-climatic descriptors and the hydrologic response descriptors. Flow duration indices (Q1...Q95) were used to represent the hydrologic responses of the study watersheds. In Part III, we also present comparisons of the hydrologic responses of the study watersheds at high flow condition, represented by the Q1 index, medium flow condition represented by the Q50 index, and low flow condition represented by the Q95 index. These comparisons revealed that: the Appalachian Plateau, ridge-dominated Ridge and Valley, and Blue Ridge watersheds have the highest Q1 and Q50 indices; the valley-dominated Ridge and Valley watersheds have the lowest Q50 index, and the Piedmont watersheds have the lowest Q1 index and a relatively high Q95 index. Finally, Part IV discusses some of the implications of the study results for watershed management. We also present applications of the research for hydrologic modeling and watershed assessment.
Keywords: Ouvrage_Collectif_Numéro1

Natural and imposed injustices: the challenges in implementing 'fair' flood risk management policy in England - Johnson, Clare L.; Penning-Rowsell, Edmund C.; Parker, Dennis J. (The Geographical Journal, 2007)
This paper examines the challenges facing English flood risk management (FRM) policy and practice when considering fair decision-making processes and outcomes at a range of spatial scales. It is recognised that flooding is not fair per se : the inherent natural spatial inequality of flood frequency and extent, plus the legacy of differential system interventions, being the cause. But, drawing on the three social justice models – procedural equality, Rawls’ maximin rule and maximum utility – the authors examine the fairness principles currently employed in FRM decision-making. This is achieved, firstly, in relation to the distribution of taxpayer’s money for FRM at the national, regional and local levels and, secondly, for non-structural strategies – most notably those of insurance, flood warnings and awareness raising, land use control, home owner adaptation and emergency management. A case study of the Lower Thames catchment illustrates the challenges facing decision-makers in ‘real life’: how those strategies which appear to be most technically and economically effective fall far short of being fair from either a vulnerability or equality perspective. The paper concludes that if we are to manage flood risk somewhat more fairly then a move in the direction of government funding of nationally consistent non-structural strategies, in conjunction with lower investment decision thresholds for other local-level FRM options, appears to offer a greater contribution to equality and vulnerability-based social justice principles than the status quo.

Race, class, and Hurricane Katrina: Social differences in human responses to disaster. - Elliott, James R.; Pais, Jeremy (Social Science Research, 2006)
Hurricane Katrina pounded the Gulf South at the end of August 2005, devastating lives and raising questions about how race and class influence human, as well as institutional, responses to disaster. This study uses survey data collected from over 1200 Hurricane Katrina survivors to examine these influences on a wide array of responses, ranging from evacuation timing and emotional support to housing and employment situations and plans to return to pre-storm communities. Results reveal strong racial and class differences, indicating that neither of these dimensions can be reduced to the other when seeking to understand responses by survivors themselves. This intersection renders low-income black home owners from New Orleans those most in need of targeted assistance as residents work to put themselves and the region back together.

Social Vulnerability to Environmental Hazards - Cutter, Susan L.; Boruff, Bryan; Shirley, W. Lynn (Social Science Quarterly, 2003)
County-level socioeconomic and demographic data were used to construct an index of social vulnerability to environmental hazards, called the Social Vulnerability Index (SoVI) for the United States based on 1990 data. Copyright (c) 2003 by the Southwestern Social Science Association.